Abnormal contractility in human heart myofibrils from patients with dilated cardiomyopathy due to mutations in TTN and contractile protein genes. Issue 1 (December 2017) - Vikhorev, Petr; Smoktunowicz, Natalia; Munster, Alex; Copeland, O'Neal; Kostin, Sawa; Montgiraud, Cecile; Messer, Andrew; Toliat, Mohammad; Li, Amy; dos Remedios, Cristobal; Lal, Sean; Blair, Cheavar; et al.
Abstract Dilated cardiomyopathy (DCM) is an important cause of heart failure. Single gene mutations in at least 50 genes have been proposed to account for 25–50% of DCM cases and up to 25% of inherited DCM has been attributed to truncating mutations in the sarcomeric structural protein titin (TTNtv). Whilst the primary molecular mechanism of some DCM-associated mutations in the contractile apparatus has been studiedin vitro and in transgenic mice, the contractile defect in human heart muscle has not been studied. In this study we isolated cardiac myofibrils from 3 TTNtv mutants, and 3 with contractile protein mutations (TNNI3 K36Q, TNNC1 G159D andMYH7 E1426K) and measured their contractility and passive stiffness in comparison with donor heart muscle as a control. We found that the three contractile protein mutations but not the TTNtv mutations had faster relaxation kinetics. Passive stiffness was reduced about 38% in all the DCM mutant samples. However, there was no change in maximum force or the titin N2BA/N2B isoform ratio and there was no titin haploinsufficiency. The decrease in myofibril passive stiffness was a common feature in all hearts with DCM-associated mutations and may be causative of DCM.